Associations between work environment and implicit rationing of nursing care: A systematic review. (17th December 2019) - Zhao, Yingnan; Ma, Dongfei; Wan, Zhenzhen; Sun, Dan; Li, Huanhuan; Sun, Jiao
Abstract: Aim: To systematically evaluate the effect of working environment on implicit rationing of nursing care. Background: Research has established direct and indirect associations between work environment and adverse patient outcomes. However, the causal nature of this relationship is uncertain, and implicit rationing has been proposed as a mediating factor between the work environment and patient outcomes. Method: Eight databases were searched for articles published between May 2000 and May 2019. Results: The reviewed articles provided evidence for the negative correlation between working environment and implicit rationing in 15 studies, and one of the studies showed that the correlation was not strong. There were differences in the levels of implicit rationing in different hospitals, units and shifts. Conclusion: The degree of influence of various factors in the working environment on implicit rationing is different. In addition, the working environment is only one of the factors that affects implicit rationing. Implications for Nursing Management: Nursing managers initiatives to improve nurses' work environments should include improve nurses' perception of the adequacy of staffing and resources and improving teamwork to decrease nursing care left undone, so as to improve nurse outcomes and quality of care.